Practicality And Effectiveness Game Snake Chemistry Ladder as a Learning Media on Material Reaction Reduction and Oxidation Class X SMA/MA - Yuliana, Yusi; Iswendi, Iswendi (FKIP - Universitas Riau, 2023)
This study is to examine the developed game snake ladder chemistry as a learning media to the real class. Objective study to disclose level practicality and level effectiveness game snake ladder chemistry as a learning medium on material Reaction Reduction and Oxidation class X MAN 1 Padang Panjang. Design study is One-Group Pretest-Posttest Design. Subject study is class X MIPA 3. Instruments study on test practicality form questionnaire practicality to teachers and participants educate and test effectiveness form question pre-test and completed post - test tested try it. Practicality data analyzed with percentage and effectiveness data with N-Gain. Based on results analysis of the data obtained, the teacher practicality is 91% (very practical) and participants educate on a small group by 86% (very practical), and test field-test obtained by 87% (very practical). Results analysis effectiveness obtained mark N-Gain by 76% with category effective. Based on results, study can conclude that game snake ladder chemistry as a learning medium on material reaction reduction and oxidation class X MAN 1 Padang Panjang very practical and effective.